Motivasi Pemuda Bekerja Sebagai Petani (Studi Kasus di Kecamatan Rancaekek, Kabupaten Bandung) - Clarisa, Decerene Ruth; Sukayat, Yayat (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
Rancaekek District still contributes to the rice production and there are still young people who involved in the agricultural sector despite the social change of the growth of industrial areas in the area. The opening of new job opportunities in Rancaekek District doesn’t necessarily make young people change professions, but they still choose to work as farmers. The research aims to find out what motivates young people to choose to work as farmers and what are the reasons underlying their choice rather than working in factories. This study employs a qualitative research design with a case study approach. Data collection using observation techniques, in-depth interviews, and library studies The determination of the research location and participant was carried out purposively. The result of the reaserch show that the main motivation of young people to work as farmers is the economic motivation which is to fulfill life’s need and there are several social motivations the environment and culture where they live, desire to connect with others, desire for increasing the sense of mutual ownership and the need among farmers, the pride of work as a farmer and the desire to live a more prosperous life. As for the reasons of partisipants to work as farmers rather than in factories is influenced by the economic factor, the amount of capital required to work in the factory, as well as the social factor which is the surplus work as the farmer seen from the freedom related to working hours and workloads.